The Analysis Of Service Quality Using Importance Performance Analysis For Mrt Jakarta - Rina Nur Chasanah; Andreas Wijaya (Fakultas Bisnis, 2020)
Public infrastructure and congestion issues become salient problems in Indonesia. According to INRIX Global Traffic Scoreboard (2018): Jakarta was ranked as twelfth worst in the world. Air quality also becoming another issues that derived from traffic congestion causing air pollution. To mitigate this issue, government has been established MRT Jakarta in 2019. This study aims to evaluate and improving service level of Moda Raya Terpadu (MRT) in order to encourage more people using public transportation, moreover altering people using public transportation would reduce the amount of fossil fuels and reducing bad air pollution for a better climate. Methodolgy of the research using service quality theory with five dimension from Parasuraman et. al, and extended in Importance Performance Analysis (IPA) method. Therefore, data was distributed using questionnaire with 18 item measurement and 102 respondents was collected. As a result, tangibility, reliability, and responsiveness dimension had been classified in quadrant one, followed assurance dimension in quadrant two, however empathy dimension had been measured in quadrant four and indicates to be improved.